2009
DOI: 10.1007/s00508-008-1122-2
|View full text |Cite
|
Sign up to set email alerts
|

Second-line treatment for Helicobacter pylori infection based on moxifloxacin triple therapy: a randomized controlled trial

Abstract: Moxifloxacin-based triple therapy is a highly effective second-line eradication treatment in H. pylori infection. Because of its high levels of safety and tolerability, this protocol represents an adequate alternative to the standard bismuth-based quadruple therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
0
21
0
3
Order By: Relevance
“…Moxifl oxacin and levofl oxacin are fl uoroquinolone antibacterial agents with a broad spectrum of activity against Gram-positive and Gram-negative bacteria and proven effi cacy in the treatment of infections of the respiratory tract, genitourinary tract, digestive tract, and skin [31,54]. Th ey have many advantages in terms of safety and simplicity dosing management [33,55]. Although our meta-analysis suggested that the eradication rates of the moxifl oxacin-based triple therapy has a slight superiority to bismuth-based quadruple therapy (OR = 1.78, 95% CI: 0.98-3.22, P = 0.06), there was no signifi cant diff erence between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moxifl oxacin and levofl oxacin are fl uoroquinolone antibacterial agents with a broad spectrum of activity against Gram-positive and Gram-negative bacteria and proven effi cacy in the treatment of infections of the respiratory tract, genitourinary tract, digestive tract, and skin [31,54]. Th ey have many advantages in terms of safety and simplicity dosing management [33,55]. Although our meta-analysis suggested that the eradication rates of the moxifl oxacin-based triple therapy has a slight superiority to bismuth-based quadruple therapy (OR = 1.78, 95% CI: 0.98-3.22, P = 0.06), there was no signifi cant diff erence between them.…”
Section: Discussionmentioning
confidence: 99%
“…Of these articles and abstracts, 17 were published in English [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and three [20][21][22] in Chinese. Th e characteristics of eligible randomized controlled trials (RCTs) are summarized in Fig.…”
Section: Characteristics Of the Articles In Our Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing a moxifloxacin-containing triple therapy plus a PPI and metronidazole with a bismuthbased quadruple therapy for 7 days, eradication rates of 73% and 54% were reported from Croatia [Bago et al 2009]. In Korea, treatment success of a second-line triple therapy (moxifloxacin, amoxicillin, and esomeprazole) was prospectively observed over a period of 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Another trial, also conducted in Korea, found that 10 days of moxifloxacin-containing triple therapy had a comparable eradication rate, with fewer side-effects and better drug compliance, to that of 14 days of bismuth-containing quadruple therapy (71.9%/82.6% vs 71.7%/90.5%, p=0.973/0.321 by ITT/PP, respectively) 14. Another trial, conducted in Austria, that compared 7 days of moxifloxacin-containing triple therapy with 7 of days bismuth-containing quadruple therapy found moxifloxacin-containing triple therapy more advantageous (eradication rates: 73.2%/78.9% vs 53.8%/64.6%, p=0.018/0.088 by ITT/PP) 16. A recent meta-analysis, which included seven randomized controlled trials, also found superior efficacy and safety for moxifloxacin-containing triple therapy compared with bismuth-containing quadruple therapy 17.…”
Section: Discussionmentioning
confidence: 99%